2001
DOI: 10.1007/s11910-001-0094-7
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, diagnosis, and treatment of nonepileptic seizures

Abstract: Psychogenic nonepileptic seizures (NES) can be classified into five categories. This review focuses on NES associated with emotional conflict, by far the most common and important group. Etiology is speculative, but the background histories of these patients are often similar. The presence of a trauma history, depression, post-traumatic stress symptoms, and the use of dissociation plus cognitive dysfunction possibly point to an organic etiology. The presentation of NES in children and adults is discussed, alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This overlap makes clinical distinction more challenging. Several differences in presentation between epileptic and nonepileptic seizures have been noted across the literature (21,22). These findings are summarized in Table 1.…”
Section: Diagnostic Challenges and The Rule Of 10smentioning
confidence: 87%
“…This overlap makes clinical distinction more challenging. Several differences in presentation between epileptic and nonepileptic seizures have been noted across the literature (21,22). These findings are summarized in Table 1.…”
Section: Diagnostic Challenges and The Rule Of 10smentioning
confidence: 87%
“…Typical PNES features include a gradual onset, long duration, waxing and waning course, and disorganized, asymmetrical motor activity [15]. PNES also lack the stereotypy of epileptic seizures; that is, the pattern of symptoms and sequence of events vary between seizures.…”
Section: Diagnosismentioning
confidence: 99%
“…Frontal lobe seizures are often mistaken for nonepileptic seizures because of their dramatic motor and vocal outbursts, possible retained consciousness and short post-ictal period. They may be distinguished from PNES by their brief duration, stereotypical nature, and tendency to begin during sleep [15].…”
Section: Diagnosismentioning
confidence: 99%
“…38 The mental health consultant can provide an assessment of the patient and the family milieu and help the treatment team with the "difficult patient." 39 It has been suggested that it is important for the mental health consultant to hold a family meeting, presenting the diagnosis and treatment options. 40 NES have also been visualized as similar to the compulsive behaviors of people with addictions.…”
Section: Treating the Patientmentioning
confidence: 99%